2012
DOI: 10.1007/s10339-012-0531-3
|View full text |Cite
|
Sign up to set email alerts
|

Do people access meaning when they name banknotes?

Abstract: Do people access the monetary value of banknotes when they say them aloud? In this study, we evaluated this question by asking people to name sequences of euro banknotes blocked by category or mixed with exemplars of other categories. The participants did not show an interference effect in the blocked context. The absence of semantic interference effect was also observed when participants named euro banknotes that did not have imprinted monetary value. These results suggest a direct connection between perceivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The answer to this question seems to be affirmative. First, we replicated the absence of semantic interference when users of the Euro currency named Euro banknotes (Macizo & Herrera, ). However, this interference effect showed up when participants named banknotes with which they did not have experience: Dollar banknotes.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The answer to this question seems to be affirmative. First, we replicated the absence of semantic interference when users of the Euro currency named Euro banknotes (Macizo & Herrera, ). However, this interference effect showed up when participants named banknotes with which they did not have experience: Dollar banknotes.…”
Section: Resultsmentioning
confidence: 94%
“…In this study, we explored whether semantic processing is required when people say aloud the monetary value of banknotes. Previous work (Macizo & Herrera, ) demonstrated that Euro banknotes can be named without semantic mediation by a direct lexical route similar to that used to name words (Damian et al ., ; Glaser, ) and digits (Herrera & Macizo, , ). The current study shows again that Euro banknotes can be named bypassing the semantic system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations